2005
DOI: 10.1021/jf051223h
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Fast Skeletal Myosin Rod and Light Meromyosin from Walleye Pollack and White Croaker:  Contribution of Myosin Fragments to Thermal Gel Formation

Abstract: Myosin rod and light meromyosin (LMM) of walleye pollack and white croaker were examined for their rheological properties by measuring dynamic viscoelastic parameters. Rods from walleye pollack and white croaker increased their storage moduli (G') in the ranges of 29-43 degrees C and 31-38 degrees C, respectively, in temperature sweep analysis. Walleye pollack LMM showed no peak of G' upon heating, whereas the white croaker counterpart exhibited a single sharp peak of G' at 35 degrees C. Loss modulus (G") show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…1). It has been reported that thermodynamic properties of the two myosins and their myosin fragments are also different from each other (Fukushima, Satoh et al, 2003;Fukushima, Yoon, & Watabe, 2003;Fukushima et al, 2005;Togashi, Kakinuma, Nakaya, Ooi, & Watabe, 2002). It is noteworthy that walleye pollack myosin unfolds upon heating at a lower temperature than that of white croaker myosin.…”
Section: Discussionmentioning
confidence: 99%
“…1). It has been reported that thermodynamic properties of the two myosins and their myosin fragments are also different from each other (Fukushima, Satoh et al, 2003;Fukushima, Yoon, & Watabe, 2003;Fukushima et al, 2005;Togashi, Kakinuma, Nakaya, Ooi, & Watabe, 2002). It is noteworthy that walleye pollack myosin unfolds upon heating at a lower temperature than that of white croaker myosin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that the gel‐forming behavior of surimi was affected largely by temperature, span of chopping, and salting time as well as by species and environment. It is, therefore, likely that not only processing conditions but the species and fish habitat temperature have also been observed to modulate the functionality of surimi (Douglas‐Schwarz & Lee, ; Fukushima et al, ; Hemung, Li‐Chan, & Yongsawatdigul, ; Poowakanjana & Park, ). The extensive culture of common carp ( Cyprinus carpio ) in Asia, Europe, Australia, and South America is due to accelerated growth rate, easy cultivation, and great feed efficiency ratio (Irawan, Vuthiphandchai, & Nimrat, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has remained ambiguous why the breaking ratio was decreased after reaching the maximum. It may be possible that hydrophobic interactions between molecules participate in such decrease (Fukushima and others ; Fukushima and others ; Phu and others ).…”
Section: Resultsmentioning
confidence: 99%
“…Actually, MTG is commercially available and possibly used for some surimi‐based products to improve their texture. Accordingly, various studies have been conducted focusing on species‐specific myosin properties and rheological profiles of thermal gels (Shimizu and others ; Fukushima and others ; Satoh and others ; Fukushima and others ; Matsuoka and others ).…”
Section: Introductionmentioning
confidence: 99%